Climate control utilizing solar powered ventilation system for parked car - Tengku Ahmad, Tengku Marissa (2013)
The heating phenomenon produces by hot weather caused the car’s compartment to gain the heat from the surrounding and the sunlight radiation, while inside the compartment will have a higher temperature compared to the outside surroundings. The high heat trapped in the enclose compartment will bring uncomfortable and suffocation feel for the driver and passengers when they enter the parked car at the open parking areas. This occurs due to the process of heat transfer from the external environment to the interior of the car. Higher air condition power is necessary to cope with this situation. However, it only functions when the engine is running. Therefore, this research intended to invent a ventilation system and use the application of solar energy as the power source during the engine is not operating. The aim of this system is to eliminate and mitigate the effects of heat in the car when parked. This research also is to determine the temperature increment inside the car compartment under direct sunlight. The heat analysis was done to determine the total heat flux produced in the parked car compartment. The value then are used to determine the flow rate, cubit feet per minutes (CFM) that needed by the ventilation fan and used to determine the sizing of the solar panel and the battery capacity. Result from this study shows that this system manages to reduce temperature inside the car compartment from 49.6°C less to 41.3°C with 53% of the effectiveness. As a conclusion, the model of the ventilation system is successfully built with the AC blowing fan and a set of electronic circuit board to control the motor level of the blower speed and powered by the solar energy. The bigger area of solar power source produces a high of electricity to generate power to ensure the system can operate with high efficiency.